The Use of Trading Strategies by Fund Managers: Some First Survey Evidence - Lukas Menkhoff; Ulrich Schmidt (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2005)
Our questionnaire survey finds that most fund managers rely on the strategies of buy-&-hold, momentum and contrarian trading. These strategies are typically applied mutually. Their use is rooted in the attributes and beliefs of the respective fund managers: buy-&-hold traders behave fundamentally oriented, risk averse and less (over)confident than others. Momentum traders appear as the least risk averse professionals going aggressively with the trend. Contrarian traders, however, show signs of overconfidence and peculiar risk aversion, both indicating difficulties in successful strategy implementation. The revealed behavioural patterns are not easily reconciled with efficient markets.
Keywords: G14; G23; 330; market efficiency; buy-&-hold strategy; momentum trading; contrarian strategy; behavioural finance